The effectiveness of hardware CPAP therapy in heart failure with preserved left ventricular ejection fraction and obstructive sleep apnea syndrome - Alexey V. Yakovlev; Ivan A. Efremov; Natalia F. Yakovlevа; Sergey N. Shilov; Andrey N. Ryabikov; Alexander T. Teplyakov; Elena V. Grakova; Kristina V. Kopeva; Ilya V. Shirokikh (Терапевтический архив, 2024)
Aim. To evaluate the effectiveness of hardware Continuous Positive Airway Pressure therapy (CPAP therapy) and its likely predictors in patients with heart failure with preserved ejection fraction (HFpEF) associated with obstructive sleep apnea syndrome (OSAS).